CATALOG OF POSITIONS AND B MAGNITUDES OF STARS IN THE CIRCUMPOLAR REGION OF NORTHEN SKY SURVEY (FON) PROJECT - Andruk, V. M.; Pakuliak, L. K.; Golovnia, V. V.; Ivanov, G. A.; Yizhakevych, O. M.; Protsyuk, Yu. I.; Shatokhina, S. V. (Одеські астрономічні публікації, 2016)
The catalog of star positions and B-magnitudes for the circumpolar region (from 58° to 90° in declination) of Northern Sky Survey project has been created under the motto of the rational use of resources accumulated in UkrVO JDA (Joint Digital Archive) in MAO NASU. The total amount of processed plates is 477. Digitizing of astronegatives has been carried out using Microtek ScanMaker 9800XL TMA and Epson Expression 10000XL scanners, with the scanning mode – 1200 dpi, the linear size of the plates – 30x30 cm or 13000x13000 px. The catalog contains 1 975 967 stars and galaxies with B ≤ 16.5m for the epoch of 1985.28. The coordinates of stars and galaxies were obtained in the Tycho-2 reference system, and B-value in the system of photoelectric standards. The internal accuracy of the catalog for all the objects is σαδ = ± 0.23 "and σB = ± 0.12m (for stars in the range of B = 8m -14m errors are σαδ = ± 0.11" and σB = ± 0.06m). Convergence between the calculated and reference positions is σαδ = ± 0.06 "(for 171 124 stars from Tycho-2), and the convergence with photoelectric stellar B-magnitudes is σB = ± 0.15m (for 5130 stars). External accuracy from the comparison with UCAC-4 is σαδ = ± 0.33 "( 1 928 367 stars and galaxies were cross identified).